Nonlinear associations of the hs-CRP/HDL-C index with metabolic dysfunction-associated steatotic liver disease and advanced liver fibrosis in US adults: insights from NHANES 2017–2018 - Bin Liang; Xue Qiu; Jiansheng Huang; Yequan Lu; Hairong Shen; Jianchao Ma; Yongyu Chen (Scientific Reports)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is a globally widespread chronic liver condition that may progress to severe liver diseases, including advanced liver fibrosis. The high-sensitivity C-reactive protein-to-high-density lipoprotein cholesterol (hs-CRP/HDL-C) index may be a potential indicator for MASLD and advanced liver fibrosis, given its relevance to inflammation and plasma lipids. In this study, the hs-CRP/HDL-C index was investigated in relation to prevalent MASLD and advanced liver fibrosis. The study analyzed secondary data from the National Health and Nutrition Examination Survey (NHANES) 2017–2018 database. The hs-CRP/HDL-C index was calculated by the quotient of hs-CRP and HDL-C. Multiple logistic regression models, Cochran-Armitage trend tests, smooth curve fitting, threshold effect analyses, and stratified analyses were used to evaluate whether the hs-CRP/HDL-C index associated with MASLD and advanced liver fibrosis. The study cohort comprised 3684 participants, of whom 1268 (34.42%) were diagnosed with MASLD and 156 (12.28%) with advanced liver fibrosis. Logistic analyses adjusted for covariates revealed positive associations of the hs-CRP/HDL-C index with MASLD and advanced liver fibrosis, consistent across all subgroups. Smooth curve fitting and threshold effect analyses revealed nonlinear relationships of hs-CRP/HDL-C index with MASLD and advanced liver fibrosis, with inflection points at 0.8 for MASLD and 1.2 for advanced liver fibrosis. Additionally, significant interactions were observed between MASLD and covariates such as gender, smoking status, chronic kidney disease (CKD), and cancer. Similarly, the hs-CRP/HDL-C index exhibited positive correlations with advanced liver fibrosis across diverse subgroups, with notable interactions related to cancer. MASLD and advanced liver fibrosis were associated with hs-CRP/HDL-C index, indicating its potential utility as a clinical marker for these conditions.